2020
DOI: 10.3389/fimmu.2020.00395
|View full text |Cite
|
Sign up to set email alerts
|

In Human Autoimmunity, a Substantial Component of the B Cell Repertoire Consists of Polyclonal, Barely Mutated IgG+ve B Cells

Abstract: B cells are critical for promoting autoimmunity and the success of B cell depletion therapy in rheumatoid arthritis (RA) confirms their importance in driving chronic inflammation. Whilst disease specific autoantibodies are useful diagnostically, our understanding of the pathogenic B cell repertoire remains unclear. Defining it would lead to novel insights and curative treatments. To address this, we have undertaken the largest study to date of over 150 RA patients, utilizing next generation sequencing (NGS) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Another explanation for the different clinical response to IRT5 treatment between environmental dry eye and Sjögren’s syndrome autoimmune mouse model may be that different immune cells are involved in each disease. While autoimmunity has substantial relation with B cells [ 40 ], the intestinal microbiome greatly influences the diversity of B cell clones controlling B cell related chronic inflammations [ 41 , 42 ]. On the other hand, environmental dry eye disease is an auto-inflammatory disease that is more associated with T cells, such as Th17 or CD4 or CD8 T cells, and so intestinal microbiome influence on B cells may be insufficient to produce significant clinical responses in dry eye diseases [ 2 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for the different clinical response to IRT5 treatment between environmental dry eye and Sjögren’s syndrome autoimmune mouse model may be that different immune cells are involved in each disease. While autoimmunity has substantial relation with B cells [ 40 ], the intestinal microbiome greatly influences the diversity of B cell clones controlling B cell related chronic inflammations [ 41 , 42 ]. On the other hand, environmental dry eye disease is an auto-inflammatory disease that is more associated with T cells, such as Th17 or CD4 or CD8 T cells, and so intestinal microbiome influence on B cells may be insufficient to produce significant clinical responses in dry eye diseases [ 2 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…A single-cell RNA sequence analysis also demonstrated expression of IL-6 and TNF-a in synovial B cells [41]. Regarding the phenotype of these cytokine-producing cells, Cowan et al showed that IgG þ CD27-B cells secreted TNF-a and were enriched in the synovium [42], while Floudas et al reported PD-1-positive B cells, which express higher levels of TNF-a and IL-6 than PD-1-negative B cells, accumulated in the joint [43]. The relevance of B cell-derived TNFa and IL-6 in the activation of synovial fibroblast was suggested by an in vitro culture system [44].…”
Section: Effector Functions Of Joint Infiltrating B Cells In Ramentioning
confidence: 99%
“…The Gini coefficient is commonly used to measure income inequality in economic studies, and it has also been used to measure the equality of distribution in individual immune repertoires (29,30). A Gini coefficient of 0 indicates equal frequencies of all clones, and a Gini coefficient of 1 indicates a monoclonal sample.…”
Section: Processing Of Raw Readsmentioning
confidence: 99%
“…A Gini coefficient of 0 indicates equal frequencies of all clones, and a Gini coefficient of 1 indicates a monoclonal sample. The Gini coefficient of each isotype was calculated using the R package immunarch and was used to compare the degree of clonal expansion in the repertoire of each sample (30).…”
Section: Processing Of Raw Readsmentioning
confidence: 99%